2018
DOI: 10.1002/jmv.25195
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence, molecular epidemiology and quantitation of parvovirus B19 DNA levels in Iranian blood donors

Abstract: Human parvovirus B19 (B19) infection is common among blood donors, and healthy blood donors can transmit virus via transfusion. Due to resistance of B19 to viral inactivation methods, there is a potential concern regarding transfusion safety in blood products. We aimed to determine the seroprevalence, molecular epidemiology, and quantitation of B19 DNA levels in blood donors in Tehran, Iran. A total of 500 blood donors from Blood Transfusion Research Center were studied. ELISA was used for detection of B19 IgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 38 publications
(55 reference statements)
1
6
0
Order By: Relevance
“…No related posttransfusion event was reported in these two studies (216,234). Similar results were reported in an Iranian study that included 500 donors, with B19V detected in plasma samples of 1.2% of individuals, with viral loads of Ͼ1E6 copies/ml, and IgG was concurrently detected in 4/6 (66.7%) cases (212). Finally, a Japanese population-based epidemiological survey of B19V infection in which B19V was screened by real-time PCR in serum samples of 2,081 individuals revealed that 0.2% of subjects were positive (210).…”
Section: Dna Viruses Double-stranded Dna Virusessupporting
confidence: 85%
See 1 more Smart Citation
“…No related posttransfusion event was reported in these two studies (216,234). Similar results were reported in an Iranian study that included 500 donors, with B19V detected in plasma samples of 1.2% of individuals, with viral loads of Ͼ1E6 copies/ml, and IgG was concurrently detected in 4/6 (66.7%) cases (212). Finally, a Japanese population-based epidemiological survey of B19V infection in which B19V was screened by real-time PCR in serum samples of 2,081 individuals revealed that 0.2% of subjects were positive (210).…”
Section: Dna Viruses Double-stranded Dna Virusessupporting
confidence: 85%
“…Nevertheless, B19V DNA can be detectable at lower viral loads in blood samples after IgG development and resolution of symptoms for prolonged periods of time (weeks to years), even in nonimmunocompromised patients. Such prolonged viremia has been described among asymptomatic blood donors with viral loads ranging from Ͻ1E3 copies/ml up to 1E6 copies/ml (212,(218)(219)(220)(221)(222)(223)(224)(225). Some data suggest that this prolonged detection of B19V DNA at low viral loads (mostly Ͻ1E3 copies/ml) might reflect the presence of naked DNA (detected by the use of more sensitive assays) rather than virions and that infections of blood product recipients are currently rare events with the use of current inactivation and other blood safety procedures (221,226).…”
Section: Dna Viruses Double-stranded Dna Virusesmentioning
confidence: 92%
“…[23] It is reported that parvovirus B19 IgG seropositivity rates vary between 6% and 82.3% in different regions of the world. [24] Parvovirus B19 prevalence slightly differs in Europe. Higher prevalence is observed in Finland, one of the Scandinavian countries, when compared to other European countries.…”
Section: Discussionmentioning
confidence: 99%
“…In the latest literature data, the presence of the B19V DNA among patients with different diseases varies—1.13% in the patients presenting with fever with or without rash, arthropathy, and chronic renal disease, and 5.1% in the patients with respiratory diseases [ 44 , 45 ]. In the research done in Iran, B19V DNA was found in 1.2% of blood donors [ 46 ].…”
Section: Discussionmentioning
confidence: 99%